2016 IEEE International Conferences on Big Data and Cloud Computing (BDCloud), Social Computing and Networking (SocialCom), Sus 2016
DOI: 10.1109/bdcloud-socialcom-sustaincom.2016.40
|View full text |Cite
|
Sign up to set email alerts
|

Online Sharing of Physical Activity: Does It Accelerate the Impact of a Health Promotion Program?

Abstract: Influence on health behavior from peers is well known and it has been shown that participants in an online physical activity promotion program are generally more successful when they share their achievements through an online community. However, more detailed insights are needed into the mechanisms that explain the influence of a community on physical activity levels (PAL). This paper discusses a detailed analysis of a data set of participants in an online physical activity promotion program. The analysis focu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Previous work has shown that the combination of participating in the program and joining the online community is associated with a small but significant average increase in PAL [11]. The objective of the current work was to demonstrate whether the dynamics of users' physical activity levels can be (partially) explained by social contagion.…”
Section: Model Simulationsmentioning
confidence: 94%
See 3 more Smart Citations
“…Previous work has shown that the combination of participating in the program and joining the online community is associated with a small but significant average increase in PAL [11]. The objective of the current work was to demonstrate whether the dynamics of users' physical activity levels can be (partially) explained by social contagion.…”
Section: Model Simulationsmentioning
confidence: 94%
“…The simple linear model describes the effect of the physical activity promotion program and the online community on the users' physical activity levels. Previous analyses have shown that this effect is an average PAL increase of 0.0005821 per day [11]. These analyses were based on a subset of users from the same data set, with all users being in their first plan and member of the community.…”
Section: Model Simulationsmentioning
confidence: 99%
See 2 more Smart Citations
“…(Rose et al, 2018). These could be helpful in removing obstacles and promoting PA, particularly when taking into account the social support qualities and group-wide possibilities of digital interventions to promote PA (Manzoor et al, 2016;Zeng et al, 2018).…”
Section: Introductionmentioning
confidence: 99%